The Effect of the Existence of Management Groups and Fees on the Functionality of Community-Based Drinking Water Supply Systems in Jayawijaya Regency - Joni Ta'dung; Mujiati Mujiati; Dewi Ana Rusim (Pelopor Publikasi Akademika, 2026)
Access to safe and sustainable drinking water remains a major challenge in rural and mountainous regions of Indonesia, including Jayawijaya Regency, Papua. Community-Based Drinking Water Supply Systems (SPAM-BM) have been developed to expand water access; however, the long-term functionality of these systems is often constrained by weak institutional management and inadequate financial sustainability. This study examined the influence of the Management Group (KP-SPAM) and community contributions on the functionality of community-based drinking water supply systems in Jayawijaya Regency.A quantitative approach was employed using stratified proportional random sampling. Data were collected from 270 respondents selected from a population of 1,312 active household connections across 18 KP-SPAM units. Data collection methods included questionnaires, observations, structured interviews, and document reviews. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination analysis.The results indicated that the Management Group variable had a positive and significant effect on SPAM functionality (? = 0.701; t = 12.467; p < 0.001), demonstrating that effective institutional management plays a crucial role in ensuring system sustainability. In contrast, community contributions did not have a significant partial effect on functionality (? = –0.092; t = –1.639; p = 0.102), although they may contribute indirectly through their relationship with management performance. Simultaneously, both variables significantly influenced SPAM functionality, explaining 42.65% of the variance in system performance.SWOT analysis further revealed that the management system is positioned in Quadrant I, indicating strong institutional capacity and favorable external opportunities. Strengthening KP-SPAM governance, enhancing financial transparency, and improving community participation are therefore recommended to ensure the sustainability of community-based drinking water services in Jayawijaya Regency.